Penguatan Kelembagaan Berbasis Tata Ruang untuk Pengembangan Desa Wisata Gosong Panjang, Kabupaten Kotabaru - Nasruddin Nasruddin; Syahlan Mattiro; Muhamad Rusmin Nuryadin; Muhammad Efendi; Wisnu Putra Danarto (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2026)
Gosong Panjang Village has outstanding potential to become a tourism village that prioritizes coastal landscapes, small islands, and local traditions. However, this development still faces institutional challenges, limited access, and a lack of basic infrastructure. The purpose of this community service program is to evaluate the cultural and natural attributes of the landscape, assess its suitability for tourism, and develop a spatial planning-based institutional strengthening plan. The method used is a field survey documented through observation, interviews, and the Village Development Plan (RPJMDes). Land suitability analysis uses scoring for seven tourism activities. The results show that the land suitability ranges from moderate to good, with beach recreation receiving the highest score. The Undulating Plain and the Coast are considered to have the best potential for land-based tourism. In the institutional strengthening strategy, funds are allocated through Pokdarwis and RPJMDes to improve road access and provide basic facilities in priority zones to support safe and sustainable village tourism development.